Diagnosis and Management of Dural Sinus Thrombosis following Resection of Cerebellopontine Angle Tumors - Moore, Justin; Thomas, Piers; Cousins, Vincent; Rosenfeld, Jeffrey V. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective Lateral sinus thrombosis is a potentially devastating but seldom studied complication of cerebellopontine angle (CPA) tumor surgery. Systemic anticoagulation in the early postoperative period has often been avoided due to the potential risks of intracranial hemorrhage.Design Retrospective review.Setting Tertiary referral center.Main Outcome Measures The goal of this study was to identify the frequency, treatment, and outcomes in patients who develop postoperative venous sinus thrombosis following CPA tumor surgery and receive early systemic anticoagulation.Results Of 43 patients with CPA tumors, we report five patients (11.6%) with transverse and/or sigmoid sinus thrombosis following resection of the tumor, four of which were detected on routine early postoperative noncontrast computed tomography (CT) scan. The thrombosis was confirmed in all cases with CT venography or magnetic resonance venography. Affected patients had significantly larger tumors than controls and tended to undergo longer operations. These patients were treated with immediate anticoagulation (intravenous heparin, followed by Coumadin for 6 months) without complication.Conclusion Venous sinus thrombosis is an underrecognized complication of CPA surgery, but it can be diagnosed in the early postoperative period by noncontrast CT imaging. Early postoperative initiation of systemic anticoagulation appears safe and effective to prevent the progression of thrombosis and its consequences.
Keywords: venous sinus thrombosis; cerebellopontine angle tumor; acoustic schwannoma; complications; anticoagulation